Government Pension Fund Thailand Environmental, Social, and Governance Weight and Score : Asset Valuation Methodology - World Bank (World Bank, Washington, DC, 2020)
As one of the largest pension funds in Thailand, government pension fund (GPF) is fully aware of its importance as a universal owner and of its role supporting sustainable global values within the context of environmental, social, and governance (ESG). In 2018, GPF publicly announced its commitment to ESG investing and its intention to be the leader in ESG investing and initiatives in Thailand. Since then, GPF has pursued its mission through co-operation with the Organization for Economic Co-operation and Development (OECD), the World Bank, and the PRI and through initiating and leading collaborative engagements with local institutional investors and with GPF’s external fund managers, both domestic and international. This document provides a detailed description of the approach, explaining how one analyze and weight ESG factors at the sectoral and at the company or issuer level, and how one incorporates these into asset valuation and pricing. The aim is to make the methodology transparent to concerned stakeholders and to share ideas to institutional investor peers.